Effects of Different Crystallization Protocols on Marginal Gap of Lithium Disilicate Single Crowns: SEM Analysis - Alon Shadur; Joseph Nissan; Diva Lugassy; Ariana Umansky; Eran Zenziper; Gil Ben-Izhack (Dentistry Journal, 2024)
Objective: In everyday dentistry, lithium disilicate is a valid option for single-fix partial dentures, and this material crystallization process is available with two protocols: long and short. This study’s aim was to assess the effects of these two different crystallization protocols, long and short, on the marginal gap of lithium disilicate single crowns. Methods: A total of 24 abutment plastic teeth were scanned using an intra-oral scanner. For each plastic tooth, an identical pair of lithium disilicate crowns was milled (a total of 48 crowns) by a four-axis machine. Each paired sample was categorized into two groups: long crystallization (24 crowns) and short crystallization (24 crowns). To assess precision, each unit’s marginal gap (including abutments and crowns) was meticulously measured at four specified regions using a scanning electron microscope. A Kolmogorov–Smirnov test performed on the study variables indicated a normal distribution (p > 0.05), and it was followed by independent t-tests (α = 0.05). Results: For the long crystallization group, the mean total marginal gap values were 42.91 ± 9.67 μm, and for the short crystallization group, the values were 43.25 ± 8.14 μm, with no significant difference between the groups (p = 0.894). In addition, no significant differences were found between the groups regarding the mean marginal gap measurements for all four surfaces (distal (p = 0.310), mesial (p = 0.732), palatal (p = 0.655), and buccal (p = 0.535)). Conclusions: Both the long and short crystallization methods used for lithium disilicate single crowns demonstrated marginal gap values of less than 120 μm, which are within the clinically acceptable range, with no significant differences across any parameters between the two groups. Regarding the marginal gap value, it is recommended to use the short crystallization protocol as it is more time-efficient.